2016
DOI: 10.1515/jpem-2014-0525
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of bone turnover in children with clinical bone fragility

Abstract: Background: The role of biochemical bone turnover markers (BTMs) in assessing low bone mass and monitoring bisphosphonate treatment in pediatric patients with clinical bone fragility is not well established. The aim of the study was to examine the correlations of BTMs and the bone mineral density (BMD), and evaluate the effects of bisphosphonates therapy on BTMs in children with clinical bone fragility. Methods: Clinical data of 115 patients with clinical bone fragility (mean age 9.7±5.8 years), 102 of whom re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…The relationship between BMD and BTM in children and adolescents with T1D has previously been investigated in a few publications and most of these could not demonstrate significant associations between BMD and BTM . In children and adolescents without T1D, the results have been more ambiguous . None of the above previously published studies have investigated the association between BTM and BMD using Z‐scores for the BTM.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between BMD and BTM in children and adolescents with T1D has previously been investigated in a few publications and most of these could not demonstrate significant associations between BMD and BTM . In children and adolescents without T1D, the results have been more ambiguous . None of the above previously published studies have investigated the association between BTM and BMD using Z‐scores for the BTM.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Serum osteokalsin düzeyi yüksek kemik dönüşümü ile karakterize durumlarda artar, büyüme atağının (Growth Spurt) gerçekleştiği puberte buna iyi bir örnektir. [2][3][4] Adölesandaki en önemli değişimlerden biri hızlı fiziksel büyümedir. Boyca büyüme hızındaki artış kızlarda 10, erkeklerde 12 yaşta başlayarak kızlarda cinsel gelişme evresi 3 veya 12 yaşta, erkeklerde cinsel gelişme evresi 4 veya 14 yaşta doruk noktasına (Peak Height Velocity) ulaşır, daha sonra hız giderek azalır ve büyüme sonlanır.…”
Section: Discussionunclassified
“…This correlation corresponded with an observed OC level decrease and body length increase during the study period. Nevertheless, serum OC level, CTx, PINP do not correlate with BMD in children with clinical bone fragility [41, 42]. Similarly, Litmanovitz et al found that changes in the biochemical markers could not predict the changes in bone strength assessed by quantitative ultrasound [43].…”
Section: Discussionmentioning
confidence: 99%